A Sociolinguistics Analysis of Edo Proverbs and Its Effects on The People, A Case Study of Ola Rotimi’s Ovoranwen Nogbaisi - Nicodemus, Emmanuel; Ojochegbe, 2Ameh Timothy (Journal Of Social Science (JoSS), 2025)
This study employs Dell Hymes ethnography of communication framework to analyse Edo proverbs in Ola Rotimi’s seminal play, OvoranwenNogbaisi (1961), a critically acclaimed work that explores the complexities of Edo culture, colonialism, and identity. Set in the precolonial Edo Kingdom, the play navigates themes of cultural resilience, power struggles and social change. Through a qualitative analysis guided by the SPEAKING model, this research reveals the pivotal role of Edo proverbs in conveying cultural values, subverting colonial narratives and shaping community norms. By examining the intersection of language, culture and power, this study contributes original insight into the functional dynamics of Edo proverbs as a communicative resource. It also contributes to the plays significance as a cultural artifact and tool for social commentary. It also contributes to the extension of Hymes framework on sociolinguistics contexts. This research fills a critical gap in sociolinguistics scholarship, offering a nuanced understanding of Edo cultural expression and its relevance to contemporary debates on identity, culture and language.